SUBALTERN PORTRAYALS IN THE HUNGER GAMES: MOCKINGJAY PART 1 MOVIE - Megawati, Indah (Elite : English and Literature Journal, 2017)
Abstract This research discussed about Subaltern Portrayal in The Hunger Games: Mockingjay Part 1 Movie produced in 2014 November which aimed to find out the social and political aspect in The Hunger Games: Mockingjay Part 1 Movie. The source of data was The Hunger Games: Mockingjay Part 1 Movie which represented subaltern. The theory used in this thesis was Gramsci’s Concept of Subaltern theory. The method used in the research was descriptive qualitative method. The researcher used note taking as instrument in order to get the valid data. As the result of the research, it was found that there were 23 subaltern portrayals in The Hunger Games: Mockingjay Part 1 Movie, they were 13 subaltern portrayals in social aspect and 10 subaltern portrayals in political aspect. The researcher concluded that the subaltern in social aspect were those who oppressed while in political aspect were those who tried to press their own claim. Abstrak Penelitian ini membahas tentang Penggambaran Subaltern dalam The Hunger Games: Mockingjay Part 1 Movie yang diproduksi pada tahun 2014 November yang bertujuan untuk mengetahui aspek sosial dan politik dalam The Hunger Games: Mockingjay Part 1 Movie. Sumber data adalah The Hunger Games: Mockingjay Part 1 Movie yang mewakili subaltern. Teori yang digunakan dalam tesis ini adalah teori Gramsci's Concept of Subaltern. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Peneliti menggunakan catatan sebagai instrumen untuk mendapatkan data yang valid. Sebagai hasil dari penelitian ini, ditemukan bahwa ada 23 penggambaran subaltern dalam The Hunger Games: Mockingjay Part 1 Movie, mereka adalah 13 penggambaran subaltern dalam aspek sosial dan 10 penggambaran subaltern dalam aspek politik. Peneliti menyimpulkan bahwa subaltern dalam aspek sosial adalah mereka yang tertindas sedangkan dalam aspek politik adalah mereka yang mencoba menekan klaim mereka sendiri.